2020
DOI: 10.9734/mrji/2020/v30i430207
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Pericopsis (Afrormosia) laxiflora (Benth.) Bark on Ringworm Germs

Abstract: Dermatophytes are responsible for ringworms that are very often found on the heads of children in Africa. In Côte d'Ivoire, ringworms have been the subject of several studies revealing fairly high frequencies. Aims: The present work consisted essentially in studying the antifungal activity of the barks of Pericopsis laxiflora, a plant from the Ivorian pharmacopoeia on germs responsible for ringworm. Methodology: The 70% hydroethanolic extract of the bark of Pericopsis laxiflora was prepared and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…[27] Activities of hydroethanolic extract of the bark of Afromosia laxiflora have also been evaluated showing it as a bioactive dermatophyte agent. [28] Overall, results from this study agree strongly with those from reported literature and thereby support the antifungal potentials of active extracts recorded with significant MICs such as F. albida, S. setigera, A. senegalensis, U. picta C. collinum, and A. laxiflora plant species. The antifungal information (data) presented herein can be exploited for their further evaluations as antimicrobial drug leads of nature.…”
Section: Minimum Inhibitory Concentration (Mic)supporting
confidence: 90%
“…[27] Activities of hydroethanolic extract of the bark of Afromosia laxiflora have also been evaluated showing it as a bioactive dermatophyte agent. [28] Overall, results from this study agree strongly with those from reported literature and thereby support the antifungal potentials of active extracts recorded with significant MICs such as F. albida, S. setigera, A. senegalensis, U. picta C. collinum, and A. laxiflora plant species. The antifungal information (data) presented herein can be exploited for their further evaluations as antimicrobial drug leads of nature.…”
Section: Minimum Inhibitory Concentration (Mic)supporting
confidence: 90%
“…They were then cut into small fragments and dried in an oven at 50°C for 5 days. These dried barks were then reduced to very fine powders which will be used for the preparation of hydroethanol extracts according to the method described by Ouattara et al 8 with some modifications. Indeed, 100 g of plant powder were shaken vigorously in 1L of 70% ethanol using an electric mixer.…”
Section: Preparation Of Hydroalcoholic Plant Extractsmentioning
confidence: 99%
“…In La Côte d'Ivoire, P. laxiflora is used traditionally to treat many health conditions including headache, stomach ulcers, stomach aches, upset stomach, gastritis, enteritis, heart pain, abdominal pain [10] while in Guinea, it is used against shigellosis and colibacillosis [11]. This plant is used for the treatment of malaria, jaundice and ulcer [12].…”
Section: Medicinal Uses Of Pericopsis Laxiflora Stem Barkmentioning
confidence: 99%
“…Ethyl acetate, methanol and aqueous crude extracts of P. laxiflora were all reported to contain tannins, flavonoids, steroids and terpenoids, cardiac glycosides, saponins, phenolic compounds, alkaloid and reducing compounds in different proportions [10].…”
Section: Chemical Compostion Of Pericopsis Laxifloramentioning
confidence: 99%
See 1 more Smart Citation